Importance of Coarse Cereals to share in food and nutritional security - Gautam, R. C. (Indian Farming, 2015)
The above analysis of nutritional value of different coarse cereals, indicate that this group of grains are contributing most significantly in the survival of human being but restricted to certain areas as ‘poor- men’s crops’. From food-security point of view, it is necessary now to enhance their per hectare productivity. As regards their contribution to total foodgrain production, the first step would be to cultivate kharif season crops like maize and sorghum intensively in irrigated rabi season also. Summer bajra cultivation is gaining momentum in the states where men’s crops’. From food-security point of view, it is necessary now to enhance their per hectare productivity. As regards their contribution to total foodgrain production, the first step would be to cultivate kharif season crops like maize and sorghum intensively in irrigated rabi season also. Summer bajra cultivation is gaining momentum in the states where irrigation facilities are provided to the farmers. This double-crop cultivation technique and other crop management practices will definitely be proved most effective in enhancing the total coarse cereal production from 42 million tonnes to 50 million tonnes by 2020.